Effects of Datomaceous Earth on the Incidence Of Sucking Pest of Guava - Das, Kishore Kumar; Swamy , GSK; Rawat, Sheetal (Bangladesh Journal of Botany, 2022)
Effects of diatomaceous earth (DE) as a source of silicon on incidence of Helopeltis antonii Signoret and Aleurodicus dispersus Russell in Guava var. Sardar were investigated. In the month of September and October maximum infestation (2.79) was observed in control plots and the least infestation (1.93) was observed in treatment with RDF + 3kg/plant of DE. In the month of November, the maximum infestation (3.62) was found in control, while the least infestation (1.89) was noticed in RDF + 3 kg/plant of DE. Again, in the month of December the maximum infestation (3.60) of tea mosquito bug was observed in the Half of RDF + 3 kg/plant of DE, followed by control (3.48) and the least infestation (2.83) was noticed in RDF + 3 kg/plant of DE. Bangladesh J. Bot. 51(4): 813-816, 2022 (December)